Pengaruh Transparansi, Partisipasi, Kompetensi Aparatur, dan Pemahaman Regulasi terhadap Akuntabilitas Dana Desa dalam Perspektif Pengendalian Internal - Vira Maulina; Ghina Haniyah; Wiwik Andriani (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2026)
This study examines the effects of transparency, community participation, village apparatus competence, and regulatory understanding on the accountability of village fund management in Tanah Datar Regency from an internal-control perspective. Data were collected during 9–15 July 2025 through a quantitative survey of 14 nagari selected purposively, with one nagari representing the highest village-fund budget in each sub-district. The unit of analysis was the individual official. Six officials directly involved in financial management were included from each nagari, resulting in 84 distributed, returned, and usable questionnaires and a 100% effective response rate. Multiple linear regression was performed using SPSS 25. The findings show that all four predictors have positive and significant associations with accountability, both partially and simultaneously. Transparency has the largest standardized beta in the estimated model (β = 0.348), followed by apparatus competence (β = 0.315), regulatory understanding (β = 0.220), and community participation (β = 0.198). The mapping of these predictors to COSO components is a conceptual interpretation used to explain plausible control mechanisms, not a direct empirical test of the effectiveness of individual COSO components. The study therefore offers a contextual contribution in the distinctive nagari governance setting and an interpretative contribution by integrating the regression findings with an internal-control perspective.